Analysis of Social Dynamics and Village Potential: Case Study in Pamriyan Village, Gemuh District, Kendal Regency - Jalaludin, Galang (Mutiara: Multidiciplinary Scientifict Journal, 2024)
In social life, the attitude of wanting to be recognized and appreciated is a common thing.From this basic need to be recognized, a feeling is born which we often call prestige. These dynamics often result in complex patterns of competition and collaboration among different groups in society (Majhi et al., 2022). This study aims to analyze the social dynamics that occur in Pamriyan Village, Gemuh District, Kendal Regency. Pamriyan Village is a rural community that has experienced various social changes due to economic developments, technology, and government policies. This study uses a qualitative approach with a case study method to deeply understand social interactions, structural changes, and adaptation of village communities to the changes that occur. Data were collected through participant observation and document analysis. The results of the study indicate that social dynamics in Pamriyan Village are influenced by internal factors such as changes in mindset and social roles, as well as external factors such as modernization and development programs. This study provides insight into how rural communities adapt to change, as well as its implications for the social structure and relationships between residents in the village.